Pengembangan Kebijakan Satu Data dalam Pelayanan Publik di Kabupaten Sleman - Triananta, Moch. Noerizza; Purnomo, Eko Priyo (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2023)
The One Data Policy aims to improve data openness practices by ensuring the availability of high-quality data to the public through open data portals, both at the national and regional levels. This research aims to evaluate efforts to develop the One Data Policy in Public Services in the Sleman Regency by analyzing six indicators: agenda setting, problem analysis, operational plans, implementation, monitoring, and evaluation. Qualitative research method with a case study approach with data sources obtained from scientific articles, mass media, and Sleman Regency regional regulatory documents. The research results show that implementing identified agenda-setting is related to inaccurate data and non-compliance with policies by increasing the capacity and quality of human resources through good governance and communication. Problem analysis highlights the importance of using actual data in decision-making. One Data Regency's operational plan facilitates access to government services even though implementation has not been evenly distributed due to digital limitations. Implementing the One Data policy in the Sleman Regency involves building communication and collaboration. Monitoring and evaluating Satu Data Sleman Regency shows that socializing policies to the community and providing incentives or sanctions to policy implementers are used to overcome obstacles. Recommendations for developing One Data in Sleman Regency by strengthening data quality, investing in human resource training, expanding digital infrastructure, better communication and collaboration, socializing policies, and a culture of using data in decision making.